2004
DOI: 10.1097/01.don.0000137633.30679.74
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome in Endodontics—The Toronto Study. Phases I and II: Apical Surgery

Abstract: This study prospectively assessed the 4 to 8 yr outcome of apical surgery performed by graduate students in phases I and II of the Toronto Study. The study cohort included 155 teeth in 138 patients. Outcome was assessed by a blinded and calibrated examiner. Clinical and radiographic measures were used for a dichotomous outcome: healed (no signs and symptoms, Periapical Index score /= 3). The recall rate was 85% and the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
172
4
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(186 citation statements)
references
References 32 publications
8
172
4
2
Order By: Relevance
“…The size of the apical lesion might also have a deleterious effect on outcomes for endodontic surgery, with larger lesions being related to less favorable healing. Among the surgical articles that stratified outcome data related to lesion size, a 5%-21% decrease in success was reported for teeth with greater than 5-mm-diameter lesions preoperatively, compared with those with lesions less than 5 mm in diameter (40,45,49,61,62). Although some individual articles reported significant differences relating to tooth type, tooth location (maxillary versus mandibular), and patient age, we did not observe clear patterns comparing the data from all the articles.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The size of the apical lesion might also have a deleterious effect on outcomes for endodontic surgery, with larger lesions being related to less favorable healing. Among the surgical articles that stratified outcome data related to lesion size, a 5%-21% decrease in success was reported for teeth with greater than 5-mm-diameter lesions preoperatively, compared with those with lesions less than 5 mm in diameter (40,45,49,61,62). Although some individual articles reported significant differences relating to tooth type, tooth location (maxillary versus mandibular), and patient age, we did not observe clear patterns comparing the data from all the articles.…”
Section: Discussioncontrasting
confidence: 56%
“…Reported success rates were 5%-27% lower for re-surgery compared with first-time surgery (56,(62)(63)(64)(65) according to most articles, with 1 article reporting 11% greater success for reoperated cases (66). A systematic review of re-surgery published in 2001 by Peterson and Gutmann (67) reported a failure rate of 38% for re-surgery, although no comparison was made to first-time surgery.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to apical surgeries, apicoectomies have a success rate of 74% and a survival rate of 91% (Wang et al, 2004). A systematic review reported that the success rate of endodontic surgery (64.2%) was significantly greater than the resurgery percentage of success (35.7%) (Peterson & Gutmann, 2001).…”
Section: Survival Ratesmentioning
confidence: 99%
“…In case of anterior teeth for which the endodontic treatment was deemed satisfactory clinically (probing) and radiologically (Type A or C), the apex was simply burnished using a ball burnisher (Wallis R ) [20,27,28]. Indirect vision was achieved with surgical micro-mirrors.…”
Section: Standardized Surgical Protocolmentioning
confidence: 99%